The Scottish Mental Health Tribunal : practice and procedure - Auchie, Derek P.; Carmichael, Ailsa (Oxford : Oxford University Press, 2020)
A full review of the Mental Health Tribunal for Scotland (Practice and Procedure) (No 2) Rules 2005 is conducted, as well as a detailed examination of the relevant provisions of the Mental Health (Care and Treatment) (Scotland) Act 2003. The authors, both Legal Members of the Tribunal, draw upon their own experiences in convening Tribunal hearings, as well as the experiences of other members, making this text an invaluable practical tool for anyone involved at any level of the Tribunal process.
Previously issued in print: Dundee: Dundee University Press, 2010.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Mental Health Tribunal for Scotland; Scotland; Mental health laws -- Scotland; Law; Laws of specific jurisdictions & specific areas of law